A toxicidade da anilina e o tingimento natural na cestaria Kaingang - Fernandes, Florêncio Rekayg; Crespim, Elvira Nivagtanh; Tiemi, Júlia (Farol, 2022)
The article reflects on experiences with natural pigments replacing aniline for dyeing Kaingang basketwork. In this way, we verified, from aesthetic experiences, the use of natural pigments in the dyeing of Kaingang basketwork as a strategy for recovering ancestral knowledge, taken from an artistic intervention with natural pigments in a Kaingang basket.
Keywords: Art Teaching; Indigenous art; Natural dyeing; Aniline